Structure of a novel Mg-rich complex compound in Mg–Co–Y ternary alloys. (15th March 2015) - Egami, M.; Abe, E.
Abstract : We have determined the structure of a novel intermetallic compound formed in Mg–Co–Y alloys, based on scanning transmission electron microscopy observations and first-principles calculations. The ternary compound forms as stoichiometric Mg30 Co2 Y9 with a large hexagonal lattice ( P 63 / mmc, a = 10.2 Å, c = 22.4 Å), and its structure is characterized by an ordered arrangement of the Co2 Y9 clusters embedded in a Mg matrix. The energetically optimized Mg30 Co2 Y9 structure appears to be highly stable with a dense-packing (73.2%) of constituent atoms.